Insecticide imidacloprid influences cognitive functions and alters learning performance and related gene expression in a rat model - Kara, Murat; Yumrutas, Onder; Demir, Caner F.; Ozdemir, Hasan Huseyin; Bozgeyik, Ibrahim; Coskun, Salih; Bal, Ramazan (Wiley, 2015)
The potential toxic effects of several pesticides, including imidacloprid on non-target organisms have not been clearly established. Also, the chronic effects of non-toxic doses on cognitive function in mammals are unknown. In this study, the effects of different doses of imidacloprid on learning and memory of infant and adult rats were evaluated, and the expressions of genes synthesizing proteins known to be associated with learning in brain tissues were also documented. 0.5, 2 and 8 mg/kg doses of imidacloprid were administered to newborn infant and adult Wistar albino rats by gavage. Their learning activities were evaluated, and the expression levels of the inotropic glutamate receptor GRIN1, synoptophysin, growth-associated protein 43 and the muscarinic receptor M1 in hippocampus were determined by real-time PCR method. Learning activities were diminished significantly at 2 and 8 mg/kg doses in the infant model groups and at 8 mg/kg dose in adult rats. Also, expression levels of GRIN1, SYP and GAP-43 were found to be insignificantly altered. Only the expression of M1 were significantly changed in high doses of adult group. Thus imidacloprid in high doses causes deterioration in cognitive functions particularly in infant rats, and this deterioration may be associated with changes in the expressions of related genes.
Keywords: cognitive function; GAP-43; GRIN 1; imidacloprid; synaptophysin; toxic effects